The Determinants That Influence The Informal Sectors - Rahmadhani, Kharisma; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The employment sector in a country is divided into two, namely the formal employment sector and the informal employment sector. Until now, the informal employment sector still dominates employment in Indonesia with a percentage of more than 50 percent. In this study, panel data analysis will be used to explain the effect of mean years of schooling, unemployment and poverty on informal employment in Indonesia from 2018 to 2022. The results of the study show that the mean years of schooling actually has a significant positive effect on the proportion of informal work. Then, unemployment and poverty have a significant positive effect on the proportion of informal employment